The Differential Role of R&D and SG&A for Earnings Management and Stock Price Manipulation* - Sun, Estelle Y. (Contemporary Accounting Research, 2021)
ABSTRACT This paper documents a differential role of R&D versus selling, general, and administrative expenses (SG&A) for real earnings management. The distinction of these two components is important because prior studies mostly examine their combined use, but firms could manipulate them differently given the differing valuation implications. Reduced SG&A is viewed positively by investors as evidence of cost reduction, while reduced R&D is viewed negatively by investors as such expenditures are critical signals of expected growth. I examine their use in the context of seasoned equity offerings (SEOs) as well as firms receiving accounting and auditing enforcement releases (AAERs). Although both groups face strong incentives to manage earnings upward by reducing expenses, I predict and find that firms will reduce SG&A but increase R&D. During the manipulation period, SEO and AAER firms exhibit lower discretionary SG&A and higher discretionary R&D, relative to control firms, and investors positively value low discretionary SG&A and high discretionary R&D. Overall, this study confirms the importance of distinguishing between R&D and SG&A in real earnings management contexts and suggests a complementary (substitutive) relation between cutting SG&A (R&D) and accruals management.